The common earth ball fungus Scleroderma citrinum Pers. newly recorded in Da Lat, Vietnam - Tham, Le Xuan (Academia Journal of Biology, 2015)
The common earth ball fungus Scleroderma citrinum Pers. newly recorded in Da Lat, Vietnam